Association between laryngoplasty and pneumonia incidence in patients with unilateral vocal fold paralysis: A Japanese insurance claims database study - Masahiro Hemmi; Daisuke Sano; Reo Tanoshima; Nobuhiko Oridate (PLoS ONE, 2026)
Objective Unilateral vocal fold paralysis (UVFP) can lead to both voice impairment and dysphagia. Previous studies have suggested that surgeries aimed at improving voice function in patients with UVFP may also incidentally enhance swallowing. However, the preventive effect of such surgeries on pneumonia remains unclear. We evaluated the impact of laryngoplasty on the incidence of pneumonia in Japan using a large employment insurance claims database of corporate employees under 75 years of age and their family members. Methods The study cohort consisted of patients diagnosed with UVFP between January 2013 and December 2022, identified from an insurance claims database. A propensity score–matched cohort was created using a 1:3 matching ratio between the treatment and non-treatment groups. Follow-up began at the index date, defined as the initial diagnosis of UVFP, and continued until the end of the study period. The primary analysis compared the cumulative incidence of pneumonia between treatment and non-treatment groups. The secondary analysis employed a self-controlled design to compare pneumonia incidence before and after laryngoplasty within treated patients. Results The full cohort included 7,641 patients with UVFP, of whom 914 comprised the matched cohort (treatment group, n = 230; non-treatment group, n = 684). The cumulative incidence of pneumonia tended to be higher in the treatment group than in the non-treatment group (hazard ratio, 1.39; 95% CI, 0.93–2.08; p = 0.098). In contrast, the self-controlled analysis demonstrated a lower pneumonia incidence after laryngoplasty compared with the pre-treatment period (incidence rate ratio, 0.36; 95% CI, 0.27–0.52; p < 0.001). Conclusions Given the discordant findings across analytical approaches, no definitive conclusion regarding a preventive effect can be drawn from the present study. Further studies are needed to evaluate long-term outcomes and to clarify causal relationships.